Deacetylation of nuclear AIF provides a braking mechanism for caspase-independent chromatinolysis and necrotic brain injury - Chen Hu; Jichuan Geng; Peipei Shan; Tongqing Zhang; Zhuqing Zhang; Xiaoyu Zhang; Menghan Lin; Xiaoxia Zhang; Dong Chang; Baokun He; Deshui Jia; Mary Zhang; et al. (Communications Biology)
Abstract Programmed necrosis involves three consecutive stages: initiation, propagation, and execution. The initiation of necrosis has been widely studied, but due to the diversity and pleiotropy of the initiating pathways, it is difficult to identify ideal targets for necrosis inhibition from upstream necrosis pathways. Genetic evidence suggests that caspase-independent chromatinolysis, an execution process in multiple forms of necrosis, could be targeted to inhibit necrosis, but its regulatory mechanisms remain unclear. Previous studies suggest that the apoptosis-inducing factor AIF promotes chromatinolysis and caspase-independent necrosis, and its cytosol-to-nucleus translocation induces irreversible chromatinolysis. Here we report that AIF acetylation at lysine 295 is required for its cytosol-to-nucleus translocation and conduction of caspase-independent chromatinolysis upon necrotic stimuli, the SIRT1 deacetylase blocks necrotic chromatinolysis via deacetylating AIF, and pharmacological activation of SIRT1 inhibits AIF-dependent chromatinolysis and necrotic brain injury. Our results reveal a reversible blocking mechanism for AIF-dependent chromatinolysis and caspase-independent necrosis, supporting that targeting the late necrosis stage is a promising therapeutic strategy for treatment of necrosis-associated diseases.